REVIEW ON SCIENTIFIC INSIGHT OF DANDRUFF/SEBORRHEIC DERMATITIS: A COMMON SKIN DISORDER - SAMUELRAJ ISAIAH; SHANMUGAM KARTHIKEYAN (International Journal of Pharma and Bio Sciences, 2015)
Dandruff is a mild form of seborrheic dermatitis, which is chronic, relapsing scalp condition and negatively generates the socio-economic impact. It is associated with an imbalance in the proportion of bacterial and fungal populations colonizing the scalp. Statistics show that 50% of the postpubertal population across the globe, irrespective of ethnicity and gender suffered with dandruff. The review article discuss in detail, the prevalence, pathophysiology, three etiologic facets of dandruff formation and its implications on the corneocynte. Despite, recent advances in the field of molecular and biochemical tools, particularly with genetic-based detection methods has greatly increased our understanding of the organisms, mechanisms, and therapeutic treatment of dandruff and seborrheic dermatitis. This article highlights the importance of research needed to understand the lack of correlation between Malassezia (formerly Pityrosporum ovale) number and the individual susceptibility on severity of dandruff. It also discusses other unexplored factors of dandruff formation.